ЎЗБЕК ХАЛҚИ ИЖТИМОИЙ-МАДАНИЙ АНЪАНАЛАРИНИНГ ЭТНОПЕДАГОГИК ВА ДИНИЙ ХУСУСИЯТЛАРИ - Хажиева, М.С. (SCIENCE and SOCIETY, 2022)
In this article, it is stated that ethnopedagogy is the source of scientific pedagogy, it allows scientists, poets and writers to choose the universal and national values necessary for modern life in the ancient pedagogical culture of the past and ethnopedagogy is the worldview, educational, and cultural heritage of a particular nation, tribe, with its own characteristics.
Keywords: ethnopedagogy; folklore; traditions; national education; Uzbek ethnopedagogy; national pedagogical ideas; customs; national traditions; national culture; science; education; poetry; music